(3QLGd UMjM eSdes - (3GdMGaX CHh HcQ CMeO Hf Ydj Hf eMeO Hf EHQGgje Hf efLhjg GdCUHgGfj GdjROj, GHf efLhjI,J (B428 (3g` s ((3GdeOQSI GdcGedjI HGdbGgQI s)
(3ChdgG (B:s
(3Chdg HYO GdOjHGLg PcQ QLGd ChQOge CHhGdMSjf eSde Hf GdMLGL GdbTjQj GdfjSGHhQj hGMJL Hge aj GdeSfO GdUMjM hcjajI QhGjJge hGdQhGI Yfge , aChd ef JjfG Hg ef CSeg CMeO s
(3GdfSNI HgG MhGTs
(3YdjgG MhGT HNW eGdcgG YHOGdbGOQ Hf eMeO GdfYjejs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs